2023
DOI: 10.1097/ju.0000000000003650
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Obesity, and Pathological Upstaging in Renal Cell Carcinoma: Results From a Large Multi-institutional Consortium

Abstract: Purpose: We sought to determine whether clinical risk factors and morphometric features on preoperative imaging can be utilized to identify those patients with cT1 tumors who are at higher risk of upstaging (pT3a). Materials and Methods: We performed a retrospective international case-control study of consecutive patients treated surgically with radical or partial nephrectomy for nonmetastatic renal cell carcinoma (cT1 N0) conducted between January 2010 and December 2018. Multivariable logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this issue of The Journal of Urology Ò , Pruthi et al (page 750), in an extensive multinational retrospective study, examined clinical risk factors and morphometric features to predict upstaging from cT1 to pT3a tumors. 2 The findings revealed that increasing preoperative tumor size, older age, and the presence of diabetes were independently associated with pT3a upstaging. Furthermore, male sex and higher BMI also showed associations with upstaging.…”
Section: Predicting Pathological Upstaging Of Renal Cell Carcinomamentioning
confidence: 89%
“…In this issue of The Journal of Urology Ò , Pruthi et al (page 750), in an extensive multinational retrospective study, examined clinical risk factors and morphometric features to predict upstaging from cT1 to pT3a tumors. 2 The findings revealed that increasing preoperative tumor size, older age, and the presence of diabetes were independently associated with pT3a upstaging. Furthermore, male sex and higher BMI also showed associations with upstaging.…”
Section: Predicting Pathological Upstaging Of Renal Cell Carcinomamentioning
confidence: 89%
“…A growing body of evidence indicates that insulin resistance (IR), which is a major component of metabolic syndrome (MS) ( 7 ), may be associated with an increased risk as well as greater mortality rates for several types of cancers ( 7 , 8 ). Metabolic syndrome comprises a cluster of metabolic abnormalities including hypertension, type 2 diabetes, obesity, and hyperlipidemia, and MS has been proven to be a risk factor for morbidity and poor prognosis of RCC ( 9 11 ). Moreover, previous studies showed that each component of MS is considered to have a close causal association with RCC ( 9 , 11 ), and the pathophysiology seems to be largely attributable to IR ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome comprises a cluster of metabolic abnormalities including hypertension, type 2 diabetes, obesity, and hyperlipidemia, and MS has been proven to be a risk factor for morbidity and poor prognosis of RCC ( 9 11 ). Moreover, previous studies showed that each component of MS is considered to have a close causal association with RCC ( 9 , 11 ), and the pathophysiology seems to be largely attributable to IR ( 12 , 13 ). Moreover, the visceral adiposity index (VAI), which is a predictor of IR, has been reported as a useful index to estimate the aggressiveness of RCC ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, Pruthi et al further show the relationship of diabetes and obesity on adverse pathological features among renal cell carcinoma patients undergoing partial or radical for clinical T1 tumors. 2 This study is important for several reasons, including being more broadly generalizable since it comes from a retrospective international cohort of patients from 11 high-volume academic hospitals. While Pruthi et al also showed that diabetes correlated with higher upstaging to pT3a for all surgical patients, diabetes and higher BMI were also associated with upstaging for only patients undergoing partial nephrectomy.…”
mentioning
confidence: 99%